Komunikasi Pengelolaan Aduan Layanan Pertanahan dan Peningkatan Citra pada Media Sosial Instagram @kementerian.atrbpn - Reza Nur Amrin; Asih Retno Dewi; Sudibyanung Sudibyanung (Jurnal Kebijakan Publik, 2025)
The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency via its Instagram account @kementerian.atrbpn uses social media to share land information and build its image. The information posted gave rise to various comments by netizens. This research aims to find out netizens' comments on posts in 2023 and the admin's response to these comments as well as finding out their efforts to improve their image in 2024. Qualitative analysis methods using media content are used in this research. A list of netizen comments and admin responses was collected through data collection, observation, and documentation studies. Netizens' comments dominate in the form of complaints and questions about land services and land mafia problems. The response often given by admins is to accept or thank them, tag the relevant work unit's Instagram account, and respond substantively. These comments are a form of community participation in the programs being held. Efforts to improve image are carried out through human resource development and collaboration, socialization of communication strategy and complaint management programs, and creation of land mafia and making contemporary posts.